ANIMATION OF BORON NEUTRON CAPTURE CANCER THERAPY - Indra Maulana (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2018)
One of the most common causes of death in the world is cancer. Scientists have been trying to find the best cure for cancer ever since it was discovered. There are some ways that are used to treat cancer patients. Lately, scientists have developed a new way in treating cancer, it’s called Boron Neutron Capture Therapy (BNCT). BNCT is a selective cancer therapy, it only selects the cancer cells to be treated and leaves the normal cell untouched. It may have no effect or only a little effect on normal cells. As new knowledge that needs to be known by all people, what is the best way to introduce BNCT? What is the best media to introduce BNCT? Is it enough to just read it in a newspaper or in a book? How about using advanced technology such as animation to introduce BNCT? The use of animation as a form of media to introduce something new is already being done in many fields. Can animation be used as a form of media to introduce BNCT too? Will it be effective? By this study, the author gives information about the effect of using animation as a tool to explain and understand BNCT more.